THE CHINESE LANGUAGE: HISTORY, CIVILIZATION, CULTURE - Kondakov, B.V.; Popov, D.S.; Chugaeva, T.N.; Kamenskikh, M.S.; Shi, Sh.; Shpak, N.E. (Perm Federal Research Centre Journal, 2016)
In this article, the status of Chinese as a world language is discussed, the peculiarities of the national, mentality, as well as the main philosophic systems, are analysed. The country’s contribution to world civilization is evaluated; the role of outstanding personalities in the development of China is shown. There is a brief outline of the history of classical and modern Chinese literature. Some issues concerning the interconnection between Standard Chinese and dialects are touched upon; the principles of hieroglyphic writing are explained. The article contains frequently used conversational phrases in Chinese which can help a person to communicate in typical situations.